Psycholinguistic Dynamics in Writing Instruction for Children with Special Needs at Tri Bhakti Al-Qudwah Inclusive Islamic Boarding School - Kholida Nur; Jauharotun Nafisah; Yuning Eka Rahma Wati; Suhono Suhono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
Writing is a fundamental literacy skill that involves complex cognitive, linguistic, motor, and socio-environmental processes, particularly for children with special needs (CSN). Research examining these psycholinguistic processes within inclusive Islamic boarding school contexts remains limited. This study aims to describe the psycholinguistic dynamics involved in writing instruction for children with special needs at Tri Bhakti Al-Qudwah Inclusive Islamic Boarding School in Metro City and to analyze the contribution of the inclusive boarding school environment to students’ writing processes. The study employed a qualitative case-study design. Participants consisted of six students with special needs, three accompanying teachers, and one boarding school administrator selected through purposive sampling. Data were collected through participant observation, in-depth interviews, document analysis, and stimulated recall, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that writing instruction involves four interconnected stages: planning, linguistic formulation, motor-tactile transcription, and monitoring and revision. Major challenges include high working-memory demands, difficulties converting phonological representations into Arabic Braille symbols, limited fine-motor coordination, and restricted revision opportunities. The inclusive boarding school environment, characterized by literacy habituation, peer tutoring, individualized assistance, and flexible learning accommodations, positively supports writing fluency and students’ confidence. The novelty of this study lies in integrating psycholinguistic analysis with the bilingual Arabic–Indonesian context of inclusive Islamic boarding school education. The findings provide pedagogical implications for developing adaptive and contextualized writing instruction models for children with special needs in inclusive Islamic educational settings.